THE CHANGES IN STREAM WATER TEMPERATURE AND WATER QUALITY PARAMETERS DURING RAINFALL EVENTS IN FORESTED WATERSHEDS: SCALING OF OBSERVATIONS - Luki Subehi; Takehiko Fukushima; Yuichi Onda; Shigeru Mizugald (Indonesian Journal of Geography, 2010)
We studied the changes in stream water temperature (Tw) and waterquality (Wq) during rainfall events in forested watersheds. The parameters ofWq(88, DOC, N03--N, DTN, Na+, 8i and r) were observedinfour regionsof Japanfrom June 2004 to December 2005. The R values between Tw and those Wqparameters and between specific discharge (Qs) and Wq were positive, exceptforthe negativeones (Na+ and Si). Similarto the relationbetweenQs vs. Tw, hystereticloops in the relations between Qs vs. those Wqparameters were clockwise,exceptfor Na+ and Si as counter-clockwiseloops. This indicatesthat the'surfaceand subsurface flows contain higher concentrations of SS, DOC, IC, N03--N andDTN. To the contrary,the deeperpathwayscontainhigherconcentrationsof Na+and Si. These results suggest that the changes in Tw and Wq could be used tointerpret theflow paths.